Application of Nanoparticles for Targeting G Protein-Coupled Receptors - Ma, Xin (Int J Mol Sci, 2018)
Nanoparticles (NPs) have attracted unequivocal attention in recent years due to their potential applications in therapeutics, bio-imaging and material sciences. For drug delivery, NP-based carrier systems offer several advantages over conventional methods. When conjugated with ligands and drugs (or other therapeutic molecules), administrated NPs are able to deliver cargo to targeted sites through ligand-receptor recognition. Such targeted delivery is especially important in cancer therapy. Through this targeted cancer nanotherapy, cancer cells are killed with higher specificity, while the healthy cells are spared. Furthermore, NP drug delivery leads to improved drug load, enhanced drug solubility and stability, and controlled drug release. G protein-coupled receptors (GPCRs) are a superfamily of cell transmembrane receptors. They regulate a plethora of physiological processes through ligand-receptor-binding-induced signaling transduction. With recent evidence unveiling their roles in cancer, GPCR agonists and antagonists have quickly become new targets in cancer therapy. This review focuses on the application of some notable nanomaterials, such as dendrimers, quantum dots, gold nanoparticles, and magnetic nanoparticles, in GPCR-related cancers.